Kontroversi Ujian Nasional Sepanjang Masa - Suke Silverius (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
The existence and application of National Examination initiate critics and controversies correlated with the National Education System Act Number 20, Year 2003 about the National Education System. The set of Critics is composed of seven disagreements linked with the national examination matter which are appraising the cognitive aspects only with the result that it cannot be used as a standard made to measure up education quality, disregarding the diversification of regional potency and of students competence, taking away the teachers’ right to do the evaluation of students achievement, establishing the evaluation based merely on the students, determining the passing grade of the examination in the absence of teachers, national and regional government take away the right of teachers in giving the diploma to the graduate students. National examination evaluates the only process of momentary and incomprehensive learning activity and at the same time neglecting educational goal orientation that brings to an end without indicating the education quality. Explication of these controversies is aimed at providing teachers and education observers the prospect of the solutions in terms of educational evaluation policy improvement for the sake of the education enhancement that have access to national development for the augmentation of people’s prosperity. ABSTRAK Keberadaan dan penerapan UN menuai kritik dan kontroversi apabila dikaitkan dengan UU Sisdiknas Nomor 20, Tahun 2003 tentang Sistem Pendidikan Nasional (Sisdiknas). Rangkaian butir-butir kritik itu terjalin dalam tujuh untaian pelanggaran UN yakni hanya mengukur aspek kognitif sehingga tidak dapat dijadikan standar untuk mengukur mutu pendidikan, mengabaikan diversifikasi potensi daerah dan peserta didik, merampas hak guru untuk melakukan evaluasi hasil belajar peserta didiknya, mendasarkan evaluasi pada peserta didik semata, penentuan kelulusan bukan oleh guru, pemerintah dan pemerintah daerah merampas hak pemberian ijazah kepada peserta didik setelah lulus ujian. UN hanya mengevaluasi hasil akhir proses pembelajaran secara momental dan tidak komprehensif serta mengabaikan orientasi tujuan pendidikan sehingga tidak mengindikasikan mutu pendidikan. Paparan kontroversi ini dimaksudkan untuk dimanfaatkan para pendidik dan pemerhati pendidikan guna menemukan solusi dalam rangka pembenahan kebijakan penilaian pendidikan demi peningkatan pendidikan yang berakses pada pembangunan nasional bangsa menuju bertambahnya kesejahteraan rakyat.